Environmental Health Risk Assessment of Carbon Monoxide Exposure for Security Guards and Ticketing Officers at Safe N Lock Sidoarjo - Nazahah Hunafa; Rachmaniyah Rachmaniyah; Rusmiati Rusmiati; Khambali Khambali (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Security guards and ticketing officers inhale the CO gas from motor vehicles, which can lead to health complaints like sore and watery eyes. The purpose of this study is to assess the health risks of CO gas exposure to the health of security guards and ticketing officers at Safe N Lock Sidoarjo. This research is descriptive, cross-sectional, and employs an ARKL approach. The population of 43 security guards and 7 ticketing officers at the same time became the sample. The research variables are CO gas concentration, temperature, humidity, wind speed, vehicle generation, fuel type, exposure frequency, exposure time, exposure duration, inhalation rate, average time period, body weight, RfC, intake, and risk characterisation. The data collection technique uses direct measurement, interview sheets, and observation. The data processing technique involves the computation of risk. We analysed the data using both univariate and risk analysis techniques. The results of the study showed an average CO concentration of 100.982 μg/m³. Security guard exposure time was 12 hours/day, while ticketing officers were 8 hours/day. Security guard exposure frequency was 261 days/year, while ticketing officers were 313 days/year. The highest duration of exposure was 25 years. The highest intake rate was 26.048 mg/kg/day with an RQ value of 0.086 mg/kg/day. The risk assessment concludes that the RQ value is less than 1, indicating a low risk of health disorders due to CO gas exposure. The researcher recommends that security guards and ticketing officers use personal protective equipment such as glasses and masks when working.